Italian young doctors' knowledge, attitudes and practices on antibiotic use and resistance: A national cross-sectional survey. (December 2020) - Di Gennaro, F.; Marotta, C.; Amicone, M.; Bavaro, D.F.; Bernaudo, F.; Frisicale, E.M.; Kurotschka, P.K.; Mazzari, A.; Veronese, N.; Murri, R.; Fantoni, M.
Highlights: A significant lack of knowledge on antimicrobial resistance (AMR) is still present. AMR was not adequately addressed during participants' medical courses. Education emerged as an essential keystone of an effective response to AMR. Stronger investments in training on AMR issues should be urgently implemented. Abstract: Objectives: Antimicrobial resistance (AMR) is one of the major health issues worldwide. Clinicians should play a central role to fight AMR, and medical training is a pivotal issue to combat it; therefore, assessing levels of knowledge, attitudes and practices among young doctors is essential for future antimicrobial stewardship (AMS) programmes. Methods: A nationwide, cross-sectional, multicentre survey was conducted in Italy. A descriptive analysis of knowledge and attitudes was performed, along with a univariate and multivariate analysis of their determinants. Results: Overall, 1179 young doctors accessed the survey and 1055 (89.5%) completed all sections. Regarding the knowledge section of the questionnaire, almost all participants declared to know the different species of bacteria proposed, however the percentage of participants who correctly responded to clinical quizzes was 23% for the question on vancomycin-resistant enterococci (VRE), 42% on carbapenem-resistant Enterobacteriaceae (CRE), 32% on extended-spectrum β-lactamase-producing enterobacteria (ESBL) and 27% on methicillin-resistant Staphylococcus aureus (MRSA). Similarly, 81% of participants disagreed in stating that AMR was adequately addressed during their medical training and 71% disagreed that they received the right example from their tutors. Finally, a high rate of agreement with the proposed actions to combat AMR was documented; in particular, the percentage agreement was 76% for respondents who agreed to be part of an active surveillance system or AMS programme. Conclusions: Tackling AMR should be a priority for politicians and for all health workers. Inclusion of competencies in antibiotic use in all specialty curricula is urgently needed.